Microbiome and response surface methodology analyses reveal Acetobacter pasteurianus as the core bacteria responsible for aerobic spoilage of corn silage (Zea mays) in hot and humid areas - Bai, Rui; Li, Haiping; Chen, Shiyong; Yuan, Xianjun; Chen, Youjun; Huang, Yanling; Zhou, Qingping; Guan, Hao (Frontiers in Microbiology, 2024)
Weak aerobic stability is a significant issue for whole-plant corn silage in hot, humid regions. Acetobacter is often seen as an indicator of aerobic deterioration in silage, but its role in fermentation and exposure, and the factors facilitating its growth, remain unclear. Bagged whole-plant corn silage was prepared with controlled dry matter (DM) content (20%, 25% and 30%) and initial Acetobacter pasteurianus concentration (40%, 50% and 60%), stored for 60 days at varying temperatures (20°C, 30°C and 40°C), then exposed to air at room temperature (20~25°C) for 7 days with or without A. pasteurianus inoculation. The findings showed A. pasteurianus did not affect the nutritional value during anaerobic fermentation, maintaining a low pH (< 3.80). However, aerobic stability decreased significantly with A. pasteurianus inoculation during air exposure. Initial microorganisms were mainly Klebsiella species, shifting to Lactobacillus and Acetobacter species after ensiling. During aerobic exposure, A. pasteurianus and A. fabarum became predominant. Response surface methodology (RSM) revealed that A. pasteurianus proliferated most at 28°C, 25% DM, and 52% initial concentration at 3 ml/kg during the aerobic phase. These findings confirm A. pasteurianus reduces aerobic stability and identify optimal conditions for its proliferation, providing a basis for preventing and controlling A. pasteurianus to improve aerobic stability in hot and humid areas.